2020
DOI: 10.1021/acsanm.9b02302
|View full text |Cite
|
Sign up to set email alerts
|

Selective Manipulation of Biomolecules with Insulator-Based Dielectrophoretic Tweezers

Abstract: Insulator-based dielectrophoretic (iDEP) trapping, separating, and concentrating nanoscale objects is carried out using a non-metal, unbiased, mobile tip acing as a tweezers. The spatial control and manipulation of fluorescently-labeled polystyrene particles and DNA were performed to demonstrate the feasibility of the iDEP tweezers. Frequency-dependent iDEP tweezers' strength and polarity were quantitatively determined using two theoretical approaches to DNA, which resulted in a factor of 2 ~ 40 differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 60 publications
(160 reference statements)
0
20
0
Order By: Relevance
“…In early 2020, Oh et al [ 123 ] reported an iDEP tweezers platform to manipulate and selectively separate DNA and polystyrene particles. The strength and polarity of the tweezers were determined numerically and experimentally.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In early 2020, Oh et al [ 123 ] reported an iDEP tweezers platform to manipulate and selectively separate DNA and polystyrene particles. The strength and polarity of the tweezers were determined numerically and experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…External AC voltage was applied on the electrodes and with the help of a fluorescence microscope, DNA manipulation was captured, as shown in Figure 10 b. The low-frequency AC voltage seems to attract DNA to the electrode (at 9 V, 80 kHz) generating a strong pDEP effect, whereas DNA was found to experience slightly reduced pDEP at the increased frequency of 120 kHz, which triggers the confined DNA to slightly move away from the electrode [ 123 ]. At 200 kHz and the same voltage of 9 V, the DNA was entirely stretched, suggesting a considerable dependence of the DEP frequency of the applied AC voltage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations